2015
DOI: 10.1186/s12889-015-2050-5
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer screening disparities among urban immigrants: a population-based study in Ontario, Canada

Abstract: BackgroundBreast cancer is one of the leading cause of mortality and morbidity in Canada. Screening is the most promising approach in identification and treatment of the disease at early stage of its development. Research shows higher rate of breast cancer mortality among ethno-racial immigrant women despite their lower incidence which suggests disparities in mammography screening. This study aimed to compare the prevalence of appropriate mammography screening among immigrant and native borne women and determi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
89
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 79 publications
(99 citation statements)
references
References 34 publications
8
89
1
1
Order By: Relevance
“…Our participation results are consistent with prior Canadian studies that have reported lower breast cancer screening rates among immigrant women and specific immigrant subpopulations 9, 10, 11, 24. Recent data from Ontario, Canada9 demonstrated that among immigrant women, South Asians had the lowest breast screening utilization rate with the age 60‐69 group demonstrating lower screening than those aged 50‐59 years.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Our participation results are consistent with prior Canadian studies that have reported lower breast cancer screening rates among immigrant women and specific immigrant subpopulations 9, 10, 11, 24. Recent data from Ontario, Canada9 demonstrated that among immigrant women, South Asians had the lowest breast screening utilization rate with the age 60‐69 group demonstrating lower screening than those aged 50‐59 years.…”
Section: Discussionsupporting
confidence: 92%
“…Our results provide additional detail, showing that participation rates are consistently poor among all countries in this regional group. Prior Canadian studies have also noted that breast screening participation is strongly associated with duration of residence in Canada 9, 10, 12, 24. Although we observed this same association within many of the immigrant groups we examined, immigrants from Iran and the UK did not show a clear association.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations